GE_GERICHTE P/1937/2018 vom 30. Januar 2020 - GE Cour de justice (2020)
ORDONNANCE PÉNALE;OPPOSITION(PROCÉDURE);CONFISCATION(DROIT PÉNAL);ARME(OBJET);DISPOSITIONS PÉNALES DE LA LARM;PRINCIPE DE LA BONNE FOI | CPP.356.al6; CPP.355.al1.leth; CPP.3.al2.leta; LArm.34.al1.lete; CP.69